Efficacy and safety of intrathecal morphine for post cesarean section analgesia - Gami, Rupesh Kumar; jahan, Kumar; Jha, Chandra Bhushan (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Government of Nepal has been conducting Cesarean section under “Safe Motherhood” program all over country. The purpose of this study was to evaluate the efficacy and safety of intrathecal morphine for post cesarean analgesia under spinal anesthesia. Methods: A total of 300 parturients posted for Cesarean section under spinal anesthesia were divided into two groups of 150 each in this prospective randomized case-control study. Morphine group received 0.15 mg of intrathecal morphine mixed in 12 mg of 0.5% bupivacaine heavy while control group received 12 mg of 0.5% bupivacaine heavy alone, after proper preparation of spinal anesthesia. The parturients were assessed for first request of analgesic as per Visual Analog Scale, frequency of analgesics required within 24 hr, nausea, vomiting, pruritus, sedation and respiratory depression. Results: Postoperative analgesia was significantly greater in morphine group as compare to control group (12.1 ± 7.6 vs 3.7 ± 2.9 hr). Frequency of analgesics requirements was also significantly lower in morphine group (1.7 ± 2.0 vs 3.4 ± 8.1). Visual Analog Scale was below 4 at most of time in morphine group. The incidence of nausea, vomiting and pruritus were more in morphine group as compare to control group but without any respiratory depression. There was no significant difference in APGAR score among fetus. Conclusion: Mixing low dose of intrathecal morphine in standard dose of spinal anesthesia effectively prolongs the duration of post cesarean analgesia and decreases the frequency of analgesics requirement without any major complication in parturients or fetus. Journal of Society of Anesthesiologists 2014 1(1): 13-17